2011
DOI: 10.2114/jpa2.30.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Hydrogen Saturated Alkaline Electrolyzed Water on Disuse Muscle Atrophy in Gastrocnemius Muscle

Abstract: The objectives of this paper were to determine the level of oxidative stress in atrophied gastrocnemius, and to verify the effect of molecular hydrogen (H 2 ) saturated alkaline electrolyzed water (HSW) on gastrocnemius atrophy by modifying the redox status, indicated by 8-hydroxy-2Ј-deoxyguanosine (8-OHdG), malondialdehyde (MDA), and superoxide dismutase (SOD)-like activity. Female Wistar rats were divided into four groups: (1) the control (CONT); (2) the Hindlimb unloading (HU, for 3 weeks) given purified no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…It has been well established that hydrogen-rich water has beneficial effects on different disease models and is mostly dependent on its anti-inflammation, 48) and antioxidative properties. 49) Hydrogen molecules also rapidly diffuse into tissues and cells and it is mild enough to disturb cellular processes. Our conjecture is that the ameliorating effect of ARW in obese mice model at least partially attributable to the existence of the dissolved hydrogen in the ARW.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that hydrogen-rich water has beneficial effects on different disease models and is mostly dependent on its anti-inflammation, 48) and antioxidative properties. 49) Hydrogen molecules also rapidly diffuse into tissues and cells and it is mild enough to disturb cellular processes. Our conjecture is that the ameliorating effect of ARW in obese mice model at least partially attributable to the existence of the dissolved hydrogen in the ARW.…”
Section: Discussionmentioning
confidence: 99%
“…Being prompted by the prominent effects of H 2 on disuse muscle atrophy, cartilage trauma, and osteopenia in animal studies 1113 , a number of clinical investigators from 2010 onwards evaluated the effectiveness of H 2 in patients suffering from different muscle and bone ailments – from sprains and strains to chronic joint disorders to myopathies 79 . Typically, these studies were designed as single-blind pilot trials, with small sample sizes (< 40 participants) and of short duration (≤ 12 weeks).…”
Section: Promising Results From Preliminary Studiesmentioning
confidence: 99%
“…Drinking enriched water ad libitum ameliorated disuse muscular atrophy after paralysis in rats [58] and protected against cardiac and kidney fibrosis by ischemic/reperfusion of kidney [59] and aging [83] in Dahl SS rats. Furthermore, chronic ad libitum drinking could reduce lipopolysaccharide-induced neuroinflammation by downregulation of TNF-α and upregulation of IL-10 in the brain, to promote recovery from sickness behavior in mice [84].…”
Section: The Hydrogen Gas Molecule As a Biological Antioxidantmentioning
confidence: 96%
“…Effects of H 2 as an antioxidant and anti-inflammatory molecule are summarized. Accumulating evidence from animal studies has revealed that H 2 is a biologically active gas, increasing antioxidative molecules, while decreasing oxidative markers, pro-inflammatory molecules, and apoptosis in affected organs and tissues possible to deliver water having 0.3-0.5 mg/L using presently available commercial electrolysis equipment [58,59]. Shirahata et al [76] and, furthermore, of hydrogen peroxide (H 2 O 2 ) are lower when compared with control water.…”
Section: The Hydrogen Gas Molecule As a Biological Antioxidantmentioning
confidence: 99%